Mehanika II - Kegl, Marko; Vesenjak, Matej; Harl, Boštjan (2020)
Mechanics II. The teaching book is devoted to the fundamentals of kinematics and dynamics of mass particles and solid undeformable bodies. At first various approaches to describe the motion of a particle and a solid body are considered. This is followed by the definition and introduction of fundamental and general laws of dynamics. This chapter concludes by the introduction of mechanical laws related to work and energy. In the second part of the book, the most interesting and more specialized topics are considered. These are related to mechanical collisions, mechanical oscillations, and analytical mechanics.
Keywords: Kinematics; Dynamics; Mass particle; Undeformable body; Mechanical laws